The causes and consequence of restatements in Indonesia - Sansaloni Butar Butar (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2018)
This study examines the causes and consequence of financial restatements in Indonesia. The first part focuses on the impact of corporate governance on restatements. Thirty six restating firmsand thirty four nonrestating firms were collected during 2010-2014. Using logistic regression, the results show that audit committeewith financial expertise is negatively related to financial restatements. On the other hand, no significant results found for board of commissioners and institutional ownership.The second part of this studyfocuses on the impact of financial restatement on management turnover. Management turnover refers to the likelihood of chief director (president director) and directors losing their jobs in 24 month periods after financial restatement. The results show that restating firms executives are more likely to lose their jobs than their counterpart in nonrestating companies. More specifically, 79% of restating companies changed their executives compares to only 38% of non-restating firms. The results of this paper would be a warning for managers to credibly report financial statements in accordance with sound accounting policies because financial restatements may cause managers to lose his job. In addition, the results are beneficial for policy makers in setting the rules to promote good corporate governance. This study determines management turnover by observing annual report. If the composition of executives in current year differs from last year, then it is decided that there has been a management turnover regardless of the causes. Subsequent research should isolate management turnover causing by other factors such as retirements. This is crucial to minimize the impact of extraneous variables.